2015
DOI: 10.1177/0022042615575373
|View full text |Cite
|
Sign up to set email alerts
|

Driven to the Bottle

Abstract: This study examines the role of workplace risk factors associated with stress, social availability, and policy enforcement in explaining the severity of alcohol misuse among truck and bus drivers. Using a sample of 227 commercial (i.e., bus and truck) drivers drawn randomly from the employees of eight Israeli transportation enterprises, findings indicate that less than 6% of drivers engage in hazardous drinking, with a far smaller proportion engaging in more risky forms of misuse (i.e., harmful or dependent dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Research conducted using dynamic panel-data analysis of US households supports previous results that overall drinking declines during economic downturns De Goeij et al [19]. Bamberger and Cohen [43] discover that a diminished economy is associated with elevated teen drinking which contradicts prior research on adults to investigate how economic factors affect teenage drug use. The majority of research indicates that alcohol intake generally promotes a cyclical lifestyle.…”
Section: Literature Reviewmentioning
confidence: 81%
“…Research conducted using dynamic panel-data analysis of US households supports previous results that overall drinking declines during economic downturns De Goeij et al [19]. Bamberger and Cohen [43] discover that a diminished economy is associated with elevated teen drinking which contradicts prior research on adults to investigate how economic factors affect teenage drug use. The majority of research indicates that alcohol intake generally promotes a cyclical lifestyle.…”
Section: Literature Reviewmentioning
confidence: 81%
“…This finding is in line with previous work demonstrating that a loss of employment leads to a decrease in income, which in turn reduces alcohol use (Davalos et al, 2012). Although some studies suggest protective effects of employment on alcohol use in which employed individuals are less likely to drink than those who are unemployed (Henkel, 2011; Popovici et al, 2012), more recent reports indicate that employment can increase alcohol use (Bamberger & Cohen, 2015; Frone, 2018). Moreover, results from the National Survey of Drug Use and Health (NSDUH) indicate that prevalence of alcohol use is higher among individuals who are employed full-time (Substance Abuse and Mental Health Services Administration, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Injunctive norms represent the extent to which members of an individual's workplace social network approve of using or working under the influence of alcohol or drugs at work. Several studies collectively supported positive associations between descriptive or injunction workplace norms and overall or workplace SI (Ames & Grube, 1999;Bacharach et al, 2002;Bamberger & Cohen, 2015;Frone, 2003;Frone & Brown, 2010;Macdonald et al, 1999). For example, using a national sample of U.S. workers, Frone and Brown (2010) found that injunctive (but not descriptive) workplace alcohol norms were positively associated with more frequent overall alcohol use and intoxication.…”
Section: Workplace Substance Use Climatementioning
confidence: 92%
“…Therefore, workplace social control refers to a broad set of work conditions that put employees at lower or higher risk of SI, such as levels of commitment or attachment to an organization, mobility during work hours, visibility of work behaviors, contact with or level of supervision, extent of formal and informal policies, and disciplinary actions regarding SI. Although several studies have shown a direct inverse association between workplace social control-in the form of supervisory policy enforcement-and employee SI (Ames et al, 2000;Bamberger & Cohen, 2015;Biron et al, 2011), others have suggested a more nuanced association. For example, using a national sample of 2,429 U.S. workers, Frone and Trinidad (2012) found no evidence linking the frequency of contact with supervisors with any of the 12 employee SI measures.…”
Section: Workplace Social Controlmentioning
confidence: 98%
See 1 more Smart Citation